2009
DOI: 10.1124/jpet.108.148106
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of the Contractile Response Mediated by Two Receptors: M2 and M3 Muscarinic Receptor-Mediated Contractions of Human Gastroesophageal Smooth Muscle

Abstract: Although muscarinic receptors are known to mediate tonic contraction of human gastrointestinal tract smooth muscle, the receptor subtypes that mediate the tonic contractions are not entirely clear. Whole human stomachs with attached esophagus were procured from organ transplant donors. Cholinergic contractile responses of clasp, sling, lower esophageal circular (LEC), midesophageal circular (MEC), and midesophageal longitudinal (MEL) muscle strips were determined. Sling fibers contracted greater than the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…We previously reported that the bethanechol-induced maximal contraction is greater in the sling muscle fibers than in all other fibers studied in these subjects (Braverman et al, 2009). This result is in general agreement with previous studies showing that human gastric sling muscle fibers contract significantly greater to acetylcholine than human clasp muscle fibers (Tian et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the bethanechol-induced maximal contraction is greater in the sling muscle fibers than in all other fibers studied in these subjects (Braverman et al, 2009). This result is in general agreement with previous studies showing that human gastric sling muscle fibers contract significantly greater to acetylcholine than human clasp muscle fibers (Tian et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Effect of the nonselective M 3 -R antagonist 4-DAMP on M 3 -R activation by BeCh in the IAS SMC. 4-DAMP caused significant and concentration-dependent rightward shift in the BeCh CRC in the IAS SMC.…”
Section: Influence Of the Selective M 3 -R Antagonist Darifenacin On mentioning
confidence: 99%
“…1). To determine whether BeCh-induced shortening of the IAS SMC is via M 3 -R activation, we examined the effect of the M 3 -R antagonist darifenacin (3,23). Darifenacin (1 ϫ 10 Ϫ9 , 3 ϫ 10 Ϫ9 , and 1 ϫ 10 Ϫ8 M) caused concentration-dependent rightward parallel shift in the BeCh CRCs.…”
Section: Influence Of the Selective M 3 -R Antagonist Darifenacin On mentioning
confidence: 99%
“…The results of the receptor density determinations are shown in Table 1 compared with our previous results in human tissue (4). As in the human tissue, the total and M 3 receptor density in the pig sling fibers were statistically significantly greater than the clasp fibers.…”
Section: Immunoprecipitationmentioning
confidence: 84%